2006
DOI: 10.3171/foc.2006.20.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive transforaminal lumbar interbody fusion: indications, technique, and complications

Abstract: ✓The authors provide an overview of the minimally invasive transforaminal lumbar interbody fusion (TLIF) procedure including indications, technique, and complications. This novel technique is a method of achieving circumferential lumbar fusion using a unilateral dorsal approach. Minimally invasive TLIF uses a tubular retractor that is inserted via a muscle-dilating exposure, thereby minimizing the approach-related morbidity. This procedure is ideal for refractory mechanical low-back and radicular pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
173
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(178 citation statements)
references
References 23 publications
3
173
0
2
Order By: Relevance
“…Symptomatic misplaced pedicle screws (2%) and cage migration (2%) were also reported. Our complication and reoperation rates appear comparable to other results of minimally invasive transforaminal lumbar interbody fusion [3,4,6,8,14,16,19,[22][23][24][25]. In the series of Rouben et al [22], the overall rate for repeat surgery (14.2%) was higher than ours.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Symptomatic misplaced pedicle screws (2%) and cage migration (2%) were also reported. Our complication and reoperation rates appear comparable to other results of minimally invasive transforaminal lumbar interbody fusion [3,4,6,8,14,16,19,[22][23][24][25]. In the series of Rouben et al [22], the overall rate for repeat surgery (14.2%) was higher than ours.…”
Section: Discussionsupporting
confidence: 86%
“…Multiple studies have reported favorable results after treatment of spondylolisthesis and other degenerative lumbar diseases with minimally invasive transforaminal lumbar interbody fusion [3,4,6,14,16,17,[20][21][22][23][24][25]. These studies described results from 6 to 49 months postoperatively; however, to our knowledge, 5-year followup data have never been reported.…”
Section: Discussionmentioning
confidence: 90%
“…Since this procedure reduces the approachrelated muscle damage, blood loss, postoperative pain, length of stay in hospital, and postoperative narcotic usage, and allows early ambulation, it is popularized by most of the spine surgeons especially when used with percutaneous pedicle screws (6,10,18).…”
Section: Sonmez E Et Al: Unilateral Percutaneous Pedicle Screw Instrmentioning
confidence: 99%
“…The authors of comparative studies involving open and MIS techniques for interbody fusion have reported complication rates that were comparable but the sizes of populations have been small and the studies were mostly retrospective or lacked a control group [1,3,7,8,14]. In some studies of less invasive techniques, however, investigators revealed an increase in perioperative morbidity, namely neurological sequelae [4].…”
Section: Complications Reoperations and Radiographic Outcomementioning
confidence: 99%
“…Several studies have reported the favorable outcomes of MIS-TLIF accompanied by spinal instrumentation with percutaneous pedicle screw insertion and decompression in degenerative spondylolisthesis [1,3,5,12,20,21,23,25]. In the presence of severe spinal canal stenosis and distorted facet anatomy due to severe FJO, MIS techniques however could limit direct visualization of neural elements and pedicle screws relative to key anatomical structures and could increase the rate of complications and pedicle screw misplacement.…”
Section: Introductionmentioning
confidence: 99%